Marriage is Scary Among Indonesian Youth: Theological and Social Perspectives - Ghazali, Muhammad; Rahmadani, Rahmadani; Pranajaya, Syatria Adymas; Suardi, Suardi; Alfiyanto, Afif; Ridho, Miftahur (FIKRAH, 2025)
The phenomenon of "Marriage is Scary" among Indonesian Muslim youth reflects the level of anxiety about the institution of marriage, despite its foundational status in Islamic theology as a sacred covenant (mithaq ghaliz) and act of worship. This study explores the theological underpinnings of these fears and examines how young Muslims reconcile divine principles with contemporary life challenges. Using a qualitative method, semi-structured interviews were conducted with 15 unmarried participants who reported anxiety or reluctance toward marriage. Thematic analysis revealed four primary factors: negative familial experiences, economic insecurity, fear of personal constraint, and exposure to negative narratives via social media. While participants acknowledged theological teachings—such as reliance on Allah (Q.S. At-Talaq: 2–3) and marriage as a Sunnah—many found these ideals difficult to apply in practice due to structural and emotional barriers. Rather than positioning Islamic theology as a prescriptive solution, the study highlights its potential as a reflective framework through which youth navigate moral ambivalence, spiritual doubt, and social transitions. The findings call for a renewed engagement with Islamic theology that addresses relational fears not only through doctrinal affirmation but through lived, contextual interpretation. This research contributes to a deeper understanding of how Islamic theological discourse interacts with personal and societal anxieties, offering a more grounded approach to addressing fears of marriage among Muslim youth in Indonesia.